(untitled) (Polish Yearbook of International Law, 2022)
This article focuses on the problems of jurisdiction in cross-border civil proceedings concerning an alleged violation of personality rights. There are no specifc rules on jurisdiction for such torts in European Union law. In the current case law of the Court of Justice of the European Union (CJEU), Art. 7(2) of the Brussels I bis Regulation is applicable to such disputes. Nevertheless, the authors argue that the CJEU has misinterpreted this article when the claim is based on violation of personality rights, and has thus created a legal chaos in such disputes. The authors analyse the peculiarities of Internet infringements and the locus delicti connecting factor in the case law of the CJEU in this area. The Court has adopted the criterion of ‘centre of interests’ as the major connecting factor to establish international jurisdiction. The authors criticize this approach and argue that it has led to a structural misunderstanding of the infringement of personality rights. Finally, the authors propose a new rule on jurisdiction in cases concerning violation of personality rights, which should be established in the Brussels I bis Regulation to ensure legal certainty and proper international dispute settlement.